Optimization of dyeing process of cotton fibers in a peruvian textile company - Crosato Oyarce, Fabiana (2024)
The textile industry is one of the most polluting industries in the world, due to the significant environmental impact it generates. Therefore, the adoption of measures to optimize its processes is necessary in order to reduce production times, as well as water and energy consumption. In this regard, this study conducted an analysis of cotton fiber production at ITESSA, a Peruvian textile company. The main objective was to optimize the dyeing process of cotton fibers using the DMAIC continuous improvement methodology. Through its implementation, it was identified that the dye used caused multiple delays in production, leading to a proposal for a change to the Grupo CHT brand dye, which allows dyeing with fewer baths and at a lower temperature without compromising color quality and intensity. With its application, the dyeing time was reduced by 10 hours, water consumption by 7500 liters, and energy usage by 38 kW-h, accompanied by economic savings for the company. The methodology presented here can be replicated in other contexts and similar companies.